Modelling the Demand for Sea Transport on the Baltic Sea - Berglund, Carl Magnus (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
The paper includes a brief presentation of the relevant background theory for the empirical work presented. It also gives an overview of some basic characteristics of the international transport flows in the Baltic Sea region. The main purpose of the paper is, however, to describe the development of a new forecasting model for sea transports in the region. Specifically, it can be used for analysis of international transport generation, its distribution or both. Effects on generation and distribution can be summarised by two elasticity measures, which are simultaneously estimable in the model. The first is an own-elasticity of transport demand, from i to j, with respect to transport cost changes on this relation. The second is a cross-elasticity of transport demand from alternative import sources, h to j, with respect to transport cost changes on the relation i to j. The empirical work in the paper is an econometric analysis of the model. The method used is non-linear regression analysis based on cross-section data.